Two-dimensional materials for anti-inflammatory applications - Rui Liu; Xinxin Zhang; Zhengbao Zha; Cheng-Yan Xu; Zhaohua Miao (Smart Materials in Medicine, 2025)
Due to unique physicochemical properties including high surface-to-volume ratio, abundant active sites, and tunable surface functionalities, two-dimensional (2D) materials have emerged as an intriguing platform for anti-inflammatory therapy. This review comprehensively explores the physicochemical characteristics, types, and anti-inflammatory mechanisms of representative 2D materials, including MXenes, black phosphorus (BP), transition metal dichalcogenides (TMDs), boron nitride (BN), metal-organic frameworks (MOFs), and layered double hydroxides (LDHs). These materials exhibit intriguing anti-inflammatory mechanisms, such as scavenging reactive oxygen/nitrogen species (ROS/RNS), regulating cytokine networks, inhibiting pro-inflammatory signaling pathways, and promoting macrophage polarization. Furthermore, their applications in treating diverse inflammatory diseases are summarized, including accelerated wound healing via ROS elimination, colitis therapy through gut microbiota modulation, mitigation of acute kidney injury (AKI) via oxidative stress reduction, and rheumatoid arthritis (RA) and neurodegenerative disorders treatment via neuroimmune regulation. Critical challenges in clinical translation, such as biodegradability and long-term biocompatibility, are addressed. This review underscores the vital role of 2D anti-inflammatory materials in bridging material science with biomedical field, offering insights into the design of future anti-inflammatory drugs.